Can the Beast be Tamed?: Reflections on John McMurtry's Unequal Freedoms: The Global Market as an Ethical System - Hodgson, Bernard J. (Journal of business ethics, 2001)
My paper responds to certain themes of Professor John McMurtry's recent book, Unequal Freedoms: The Global Market as an Ethical System. Although I am in general sympathy with McMurtry's penetrating critique of conventional market theory and practice, I find Unequal Freedoms ambivalent on the critical question of whether endorsing and enacting the life-value code McMurtry proposes would require only a mitigation of the principles and definitive activities of the competitive market system or whether significant reforms within the system would have to be deep structural ones. It is argued that the second alternative is inescapable. I defend my perspective from the point of view of a philosophical analysis of orthodox or neo-classical theory-construction about the competitive market order. In particular, I examine three fundamental principles of such modelling: the maximization of the satisfaction of self-interest, the unboundedness of consumer desire for material goods, and the distribution of monetized wealth. In order for McMurtry's "civil commons" to survive, the practice of each of these principles would need to be radically modified. However, in doing so, competitive capitalism would lose its essential identity as a socio-economic order.